Study of ionized diffuse gas in edge-on galaxies - Souza Mendes, Janayna de; Vale Asari, Natalia (Cadernos de Astronomia, 2024)
One of the main components of a galaxy is gas, which can be found in different densities and ionized by different sources. The extraplanar diffuse ionized gas (DIG), the one with the lowest density located outside the plane, does not yet have its main sources of ionization well understood, which is the objective of this study. Using full-field spectroscopy data from eight edge-on galaxies obtained with the Multi-Unit Spectroscopic Explorer instrument on the Very Large Telescope (MUSE/VLT), we analyze the behavior of emission line ratios in function of the distance z to the galactic plane. Our objective is to investigate two main sources of ionization in the extraplanar DIG: escaping radiation from regions with star formation, and hot low-mass evolved stars (HOLMES). Among our sample, we carried out a preliminary analysis of the extraplanar DIG of the galaxy ESO157-49. The Hα equivalent width values of this object fall with distance from the plane, indicating that photon escape plays a smaller role in this region. Furthermore, line ratios such as [N II]/Hα and [S II]/Hα increase to great heights, and if combined with high values of [O III ]/Hβ , suggests the existence of harder ionizing sources such as HOLMES. To quantify the contribution of each of the proposed ionizing sources, we will compare our observational measurements of emission lines with theoretical models of photoionization.